Silicon might mitigate nickel toxicity in maize roots via chelation, detoxification, and membrane transport - Olha Lakhneko; Ivana Fialová; Roderik Fiala; Mária Kopáčová; Andrej Kováč; Maksym Danchenko (Ecotoxicology and Environmental Safety)
Nickel is an essential micronutrient for plant growth and development. However, in excessive amounts caused by accidental pollution of soils, this heavy metal is toxic to plants. Although silicon is a non-essential nutrient, it accumulates in most monocots, particularly the vital crop maize (corn, Zea mays). In fact, this metalloid mineral can alleviate the toxicity of heavy metals, though the mechanism is not entirely clear yet. Herein, we measured proteome, gene expression, enzyme activities, and selected sugars to investigate such effect thoroughly. Deep proteomic analysis revealed a minor impact of 100 µM Ni, 2.5 mM Si, or their combination on roots in 12-day-old hydroponically grown maize seedlings upon 9 days of exposure. Nonetheless, we suggested plausible mechanisms of Si mitigation of excessive Ni: Chelation by metallothioneins and phytochelatins, detoxification by glycine betaine pathway, and restructuring of plasma membrane transporters. Higher activity of glutathione S-transferase confirmed its plausible involvement in reducing Ni toxicity in combined treatment. Accumulation of sucrose synthase and corresponding soluble sugars in Ni and combined treatment implied high energy requirements both during heavy metal stress and its mitigation. Expression analysis of genes coding a few differentially accumulated proteins failed to reveal concordant changes, indicating posttranscriptional regulation. Proposed mitigation mechanisms should be functionally validated in follow-up studies.